Manajemen Pembelajaran Berbasis Bahtsul Masail Pada Mata Pelajaran Fiqih Ibadah di Pondok Pesantren Fathul Ulum Jombang - Mihmidaty Ya'cub; Nurul Lailiyah; Nur Hani’ah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
This research is to find out the implementation of bahtsul masail in Fathul Ulum boarding school Jombang, the students’ critical thinking of fiqh, and the implementation of bahtsul masail in increasing the critical thinking of ulya class students in the subjects fiqh of worship. This research is a descriptive qualitative method using a case study design, about how the implementation of Bahtsul Masail in increasing the critical thinking of ulya class students in fiqh worship subjects. The results of research show that: 1) the implementation of bahtsul masail is held once a week on bahtsul masail sughra and once a month in bahtsul masail Kubra. 2) Students’ critical thinking in fiqh subjects is seen when students can describe the problem, criticize the problem and provide answers in accordance with the problems proposition, especially religious jurisprudence issue occurs in the community. 3) The implementation of bahtsul masail at the Fathul Ulum Jombang has increased; students have begun to be critical of the problems arround them. The form of implementation has been carried out in Fathul Ulum Jombang is about the issue of ablution, prayer, and so on.